Design and simulation of a new type of 500 MHz single-cell superconducting RF cavity - 陆昌旺 刘建飞 侯洪涛 马震宇 毛冬青 封自强 赵申杰 罗琛 赵玉彬 张志刚 郑湘 韦业龙 于海波 李正 徐凯 (Chinese physics C, 2012)
This paper illustrates the design and simulation of a unique 500 MHz single-cell superconducting radio frequency cavity with a fluted beam pipe and a coaxial-type fundamental power coupler. The simulation results show that the cavity has a high r/Q value, a low peak surface field and a large beam aperture, so it can be a candidate cavity for high current accelerators. With the help of a fluted beam tube, almost all the higher order modes can propagate out of the cavity, especially the first two dipole modes, TE 111 and TM 110 , and the first higher monopole mode, TM 011 . The external quality factor of the coaxial fundamental power coupler is optimized to 1.2 × 10 5 , which will be useful when it is applied in the light source storage ring.